Creep rupture of nanocomposites. - Foo, Jing Jing. (2009)
Carbon nanotubes have been the limelight in the current research field soon after their discovery. The study of these cylindrical, carbon-based molecules has led to numerous findings of their multifunctional properties – high strength, high stiffness, high flexibility, low density, and good electrical and thermal conductivities. These extraordinary properties of the nanotubes would provide tremendous opportunities for the development of new material systems and create a wide variety of potential technological applications. The mechanical properties of carbon nanotubes, in particular, have been studied extensively as they offer scope for the development of carbon nanotube-reinforced composites. Yet the question on the long term behavior of these nanotubes under prolonged mechanical loading remains unanswered today. The aim of this project is to investigate the creep behavior of single-walled carbon nanotubes (SWNTs) embedded in epoxy matrix. In this report, a concise literature review on the background and mechanical properties of carbon nanotubes as well as their applications is presented. It is found from experimental results that the SWNT/epoxy composites have higher ultimate stress than that of neat epoxy and the time to failure of the composites is much longer given the same applied stress. The results are also compared to the SWNT bundles and suggested that under low stress levels, the SWNTs in composites survived longer than that of the bundles alone.